The transdisciplinary studio - Coles, Alex. (Berlin : Sternberg Press, 2012)
Artists and designers are now defined not by their discipline but by the fluidity with which their practices move between the fields of architecture, art, and design. This volume delves into four pioneering transdisciplinary studios-Jorge Pardo Sculpture, Konstantin Grcic Industrial Design, Studio Olafur Eliasson, and Åbäke-by observing and interviewing the practitioners and their assistants. A further series of interviews with curators, critics, anthropologists, designers, and artists serves to contextualize the transdisciplinary model now at the fore of creative practice. Including interviews with Jorge Pardo, Konstantin Grcic, Olafur Eliasson, and Åbäke; and Vito Acconci, Gui Bonsiepe, James Clifford, Dexter Sinister, Martino Gamper, Ryan Gander, Caroline Jones, Ronald Jones, Maria Lind, Alessandro Mendini, Rick Poynor, and Andrea Zittel.
boek
Keywords: Artists' studios; Architectural studios; Architecture -- Philosophy; Art -- Philosophy; Art and design; Pardo, Jorge, -- 1963-; Grcic, Konstantin, -- 1965-; Ólafur Elíasson, -- 1967-; Åbäke (Artist group)